Borobudur temple and the megalith villages of the Ngadha and Manggarai in the light of Indonesia’s tourist promotion; A legacy of colonial representation - Sudarmadi, Tular (UI Scholars Hub, 2023)
As a foreign exchange earner for the Indonesian government, the tourism industry has currently prioritized ten tourist destinations. Problematically, this promotion of the beauty and diversity of nature and ethnicty marginalizes and exoticizes a number of ethnic group and their areas. This promotion, which can be traced back to colonial times, still reflects the Dutch colonial legacy, particularly Darwinian social evolution. To clarify this situation, this article illustrates tourism promotion in the historical and socio-cultural contexts of Borobodur in Java and the megalith villages of the Ngadha and Manggarai people of Flores. It investigates the representation and articulation of colonial perceptions which influence tourist promotion programmes, and their impact on the perceptions of tourists and local residents. An examination of the formation of the Indonesian tourist industry also reveals between the Dutch colonial control of knowledge, the vision of the Indonesian government, tourists desires, and local stakeholder expectation of this promotion. It ends with an outline of the efforts of local residents in the megalithic villages in Flores to decolonize the tourism promotion narratives of the Indonesian government.